2019
DOI: 10.1002/anie.201814489
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecule Permeation across Membrane Channels: Chemical Modification to Quantify Transport across OmpF

Abstract: Biological channels facilitate the exchange of molecules across membranes,b ut general tools to quantify transport are missing. Electrophysiology is the method of choice to study the functional properties of channels.However, analyzing the current fluctuation of channelstypically does not identify successful transport, that is,d istinguishing translocation from binding.T odistinguish both processes,weadded an additional barrier at the channel exit acting as am olecular counter.T oi dentify permeation, we compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 35 publications
1
33
0
3
Order By: Relevance
“…In Figure S7 of the SI, a linear fit of the rates at lower voltages is shown on a semi-log scale, suggesting a permeation rate of 1-2 Ptm molecules per second for a 1 µM gradient at 0 V, where the permeation time for individual events is estimated from a logarithmic plot as 20-25 ms. Astonishingly, this flux rate agrees nicely with that estimated from the initial rates obtained by the ensemble fluorescence assays in vesicles (see above). In a second set of electrophysiological measurements, we characterized the concentration-driven relative permeation by using the so-called reversal potential measurement technique [31,32] (see Section 2 in the SI for details on Material and Methods). Starting with two compartments having 0.1 mM potassium sulfate separated by a ΔCymA channel embedded in a DPhPC bilayer, a concentration gradient of 0.25 mM Ptm sulphate was introduced on the cis side.…”
Section: Figure 3: A) Ion Current Traces Of a Single Reconstituted ∆Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure S7 of the SI, a linear fit of the rates at lower voltages is shown on a semi-log scale, suggesting a permeation rate of 1-2 Ptm molecules per second for a 1 µM gradient at 0 V, where the permeation time for individual events is estimated from a logarithmic plot as 20-25 ms. Astonishingly, this flux rate agrees nicely with that estimated from the initial rates obtained by the ensemble fluorescence assays in vesicles (see above). In a second set of electrophysiological measurements, we characterized the concentration-driven relative permeation by using the so-called reversal potential measurement technique [31,32] (see Section 2 in the SI for details on Material and Methods). Starting with two compartments having 0.1 mM potassium sulfate separated by a ΔCymA channel embedded in a DPhPC bilayer, a concentration gradient of 0.25 mM Ptm sulphate was introduced on the cis side.…”
Section: Figure 3: A) Ion Current Traces Of a Single Reconstituted ∆Cmentioning
confidence: 99%
“…Studien wurde ein ähnlicher Tr end fürd ie Permeation kürzerer Polyargininmoleküle durch hetero-oligomere Kanäle und durch den allgemeinen Diffusionskanal OmpF beobachtet. [28] In einer zweiten Serie elektrophysiologischer Messungen haben wir die konzentrationsbedingte relative Permeation mithilfe der so genannten Umkehrpotential-Messtechnik charakterisiert [29,30] (Einzelheiten in Material und Methoden, siehe Abschnitt 2d er SI). Ausgehend von zwei Kompartimenten mit 0,1 mm Kaliumsulfat, die durch einen in eine DPhPC-Doppelschicht eingebetteten DCymA-Kanal getrennt waren, wurde auf der cis-Seite ein Konzentrationsgradient von 0,25 mm Ptm-Sulfat angelegt.…”
Section: Forschungsartikelunclassified
“…The material of choice is of paramount importance for the nanochannel surface characteristics, which can, eventually, be modified through inorganic, [50] organic [50] or biological molecules. [51] Finally, the bonding step, which is needed to close the top-down fabricated nanofluidic channels can easily destroy the devices.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the top‐down techniques require a limited set of materials (mainly PDMS, SiO 2 , Si, selected photoresists and a few others). The material of choice is of paramount importance for the nanochannel surface characteristics, which can, eventually, be modified through inorganic, organic or biological molecules . Finally, the bonding step, which is needed to close the top‐down fabricated nanofluidic channels can easily destroy the devices.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] In particular, major outer membrane channels such as OmpF and OmpC from E. coli are part of the pathway of antimicrobial influx. [10][11][12][13][14] The high-resolution crystal structure showed that OmpF is composed of three identical water-filled monomers. [15] Each monomer contains 16-antiparallel b-sheets spanning in the membrane domain.…”
mentioning
confidence: 99%